2021
DOI: 10.1016/j.dib.2021.107330
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data-sets on sex reversal and histopathological assessment of potential endocrine disrupting effects of graphene oxide on Japanese medaka (Oryzias latipes) larvae at the onset of maturity

Abstract: The datasets of this article present the experimental parameters resulting from the assessment of sex reversal (SR) as a biomarker of endocrine disrupting effect of graphene oxide (GO), together with the histopathological assessment of ovary, testis, liver and kidneys of medaka larvae. These data sets support the published article “Sex-reversal and histopathological assessment of potential endocrine-disrupting effect of graphene oxide on Japanese medaka ( Oryzias larvae ) larvae.” The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…16 Our laboratory has been evaluating GO, as a potential EDC using Japanese medaka fish (Oryzias latipes), as our experimental model. [17][18][19][20][21][22][23] We have demonstrated that the males of medaka fish are more sensitive to GO than the females. From our histopathological evaluation of the gonadal structures and thyroid follicles, we found that the damages observed after GO administration was mainly due to aggregation/agglomeration of GO on or within the organs rather than directly acting as an EDC.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…16 Our laboratory has been evaluating GO, as a potential EDC using Japanese medaka fish (Oryzias latipes), as our experimental model. [17][18][19][20][21][22][23] We have demonstrated that the males of medaka fish are more sensitive to GO than the females. From our histopathological evaluation of the gonadal structures and thyroid follicles, we found that the damages observed after GO administration was mainly due to aggregation/agglomeration of GO on or within the organs rather than directly acting as an EDC.…”
mentioning
confidence: 85%
“…The solution of GO (both 20 and 2000 mg/L) was sonicated for 5 min (2 s on -1 s off pulse, 225 w) using a probe sonicator (ultrasonicator LPX 750, Cole Palmer, Chicago, IL) in ice temperature and further diluted to desired concentration when necessary (for larvae). The sonicated nanomaterial was further checked by transmission electronmicroscope at the Electron Microscopy Core laboratory at the Jackson State University, Jackson, MS. [18][19][20][21]…”
Section: Go Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal maintenance and details of the medaka colony maintained at the Medaka fish culture facility at the Jackson State University were described previously [1] , [2] – 3 , 5 , 6] . Briefly, the breeding colony of Japanese medaka fish (orange red varieties, Hd-rR strain) was maintained in the Aquatic Toxicology Laboratory at the Plant Science building at Jackson State University, Jackson, MS, USA.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The trunk was used for studies on gas gland cells. The phenotypic sex was determined by gonad histology and genotypic sex by genotyping sex-specific male gene dmy [1] , [2] , [3] . Description of data collection GO was obtained from Sigma (St. louis MO), and sonicated in ERM.…”
Section: Specifications Tablementioning
confidence: 99%